2003
DOI: 10.1097/01.psy.0000079378.39062.d4
|View full text |Cite
|
Sign up to set email alerts
|

Altruistic Social Interest Behaviors Are Associated With Better Mental Health

Abstract: Helping others is associated with higher levels of mental health, above and beyond the benefits of receiving help and other known psychospiritual, stress, and demographic factors. The links between these findings and response shift theory are discussed, and implications for clinical interventions and future research are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
168
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(194 citation statements)
references
References 31 publications
21
168
0
5
Order By: Relevance
“…close relationship or stranger), and the severity of the recipient's problem may all influence the providers' psychological wellbeing in the course of supporting others (Clark & Reis, 1988;Nijboer et al, 1999). For instance, a community-based study of the benefits of helping others suggested that when care tasks overwhelmed the provider, the support appeared to be negatively associated with the helper's mental health (Schwartz et al, 2003). Therefore, future research aimed at stress-specific (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…close relationship or stranger), and the severity of the recipient's problem may all influence the providers' psychological wellbeing in the course of supporting others (Clark & Reis, 1988;Nijboer et al, 1999). For instance, a community-based study of the benefits of helping others suggested that when care tasks overwhelmed the provider, the support appeared to be negatively associated with the helper's mental health (Schwartz et al, 2003). Therefore, future research aimed at stress-specific (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Social connectedness may play a more important role later in the recovery process, and may be more relevant for mental health outcomes rather than disability outcomes. In past research in adults, such altruistic social interest behaviors were associated with higher levels of mental health [22], and lower mortality [23], and males and females seemed to have different aspects of well-being associated with such behaviors [20].…”
Section: Discussionmentioning
confidence: 99%
“…According to a small body of literature that explores the phenomenon of helping others, engaging in such activities could actually serve to help improve psychological well-being for individuals, regardless of their level of adaptation. It is important to note, however, that helping others may not be appropriate for everyone; that feeling overwhelmed by the demands of others and giving beyond one's resources may have a negative effect [Schwartz, et al, 2003]. …”
Section: Discussionmentioning
confidence: 99%